2007
DOI: 10.2174/138527207779316453
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Selective Additions of Organometal Reagents to Carbonyl Compounds

Abstract: Carbon-carbon bond forming reactions are simple and direct methods for synthesizing the various skeletons and the diverse structures of organic compounds. Even 100 years after the discovery of the Grignard reaction, organomagnesium, organolithium, and organoaluminum remain popular for carbon-carbon bond formation reactions in modern organic chemistry. Moreover, asymmetric alkyl-or aryl-additions to carbonyl compounds with organometal reagents is attractive due to the enantioselective synthesis of chiral second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(38 citation statements)
references
References 102 publications
(123 reference statements)
0
38
0
Order By: Relevance
“…[1][2][3][4] Over the past two decades, a variety of chiral ligands have been developed to deliver desired alcohols in high enantioselectivities. [5][6][7][8][9][10][11][12][13][14][15][16] Recent studies have shown that organoaluminum compounds are effective reagents, [17][18][19][20][21][22][23][24][25][26][27][28][29] and addition reactions can even be completed in 10 min.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4] Over the past two decades, a variety of chiral ligands have been developed to deliver desired alcohols in high enantioselectivities. [5][6][7][8][9][10][11][12][13][14][15][16] Recent studies have shown that organoaluminum compounds are effective reagents, [17][18][19][20][21][22][23][24][25][26][27][28][29] and addition reactions can even be completed in 10 min.…”
Section: Introductionmentioning
confidence: 99%
“…24 Grignard [30][31][32][33] and lithium 34 reagents have also been established recently as efficient nucleophiles for addition reactions despite their high reactivity. In these studies, a presence of diamine additive and/or excessive amounts of Ti(O-i-Pr) 4 were used to deactivate the high reactivity of the Grignard and lithium reagents. The presence of excess Ti(Oi-Pr) 4 is a general feature of titanium-catalyzed addition reactions for products achieving high enantioselectivities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12] Additionally, the reaction leads to secondary alcohols, which are valuable chiral building blocks 13,14 for the preparation of natural products or new materials with interesting physicochemical properties, 2,9 such as chiral liquid crystals 15 (Scheme 1). Although many chiral ligands for the reaction have been described so far, most of them being N,N-dialkyl amino alcohols (e.g.…”
Section: Introductionmentioning
confidence: 99%